Inner structure- and surface-controlled hollow MnO nanocubes for high sensitive MR imaging contrast effect - Kukreja, Aastha (Nano Converg, 2020)
Manganese oxide (MnO) nanocubes were fabricated and their surface were modified by ligand encapsulation or ligand exchange, to render them water-soluble. And then, MnO formed the hollow structure by etching using acidic solution (phthalate buffer, pH 4.0). Depending on the ligand of the MnO surface, it increases the interaction between MnO and water molecules. Also, the hollow structure of MnO, as well as the ligand, can greatly enhance the accessibility of water molecules to metal ions by surface area-to-volume ratio. These factors provide high R1 relaxation, leading to strong T1 MRI signal. We have confirmed T1-weighted MR contrast effect using 4-kinds of MnO nanocubes (MnOEn, MnOEnHo, MnOEx and MnOExHo). They showed enough a MR contrast effect and biocompatibility. Especially, among them, MnOExHo exhibited high T1 relaxivity (r1) (6.02 mM(−1) s(−1)), even about 1.5 times higher sensitivity than commercial T1 MR contrast agents. In vitro/in vivo studies have shown that MnOExHo provides highly sensitive T1-weighted MR imaging, thereby improving diagnostic visibility at the disease site. [Image: see text]